Optimization of Cable Harness AssemblySystems Based on Lean Concept Application - Klašnja, Nataša; Sremčev, Nemanja; Vukelić, Djordje; Simeunović, Nenad; Lazarević, Milovan (International Journal of Industrial Engineering and Management, 2019)
TIn this writing paper an analysis of production system for assembly of cable harness from the point of the time for assembly and losses in working process has been implemented. A suggestion has been made according to a methodology for advancement in assembly system based on Lean concept. Based on this suggested methodology an optimization of numbers of working stations has been executed. The obtained results point out that efficient implementation of Lean concept in assembly process of cable harness is possible. At the end are given the appropriate conclusions and directions of future researches. Article history: Received (15.07.2018); Revised (23.09.2018); Accepted (27.09.2018)